2015
DOI: 10.1182/blood-2015-04-639336
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted therapy for early-stage extranodal nasal-type NK/T-cell lymphoma: analysis from a multicenter study

Abstract: Key Points• Patients with early-stage extranodal nasal-type NKTCL were classified as low risk or high risk using 5 independent prognostic factors.• Risk-adapted therapy of RT alone for the low-risk group and RT consolidated by CT for the high-risk group proved the most effective treatment.The optimal combination and sequence of radiotherapy (RT) and chemotherapy (CT) for extranodal nasal-type natural killer/T-cell lymphoma (NKTCL) are not well-defined. The aim of this study was to create a risk-adapted therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(177 citation statements)
references
References 59 publications
5
169
2
1
Order By: Relevance
“…Kaplan-Meier analysis showed that OS was associated with Ann Arbors stage and RT (p < 0.05), but not associated with sex, age at diagnosis, race, era of diagnosis, histology and B symptoms (p > 0.05). It was consistent with the previous literature reports [12,21,22,[28][29][30][31][32]. Multivariate Cox regression analysis revealed that Ann Arbor stage and RT were both significantly associated with OS and CSS (p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Kaplan-Meier analysis showed that OS was associated with Ann Arbors stage and RT (p < 0.05), but not associated with sex, age at diagnosis, race, era of diagnosis, histology and B symptoms (p > 0.05). It was consistent with the previous literature reports [12,21,22,[28][29][30][31][32]. Multivariate Cox regression analysis revealed that Ann Arbor stage and RT were both significantly associated with OS and CSS (p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Currently, radiotherapy (RT) is the most widely used treatment for patients with early-stage ENKTL. Depressingly, the clinical efficacy of RT reported was controversial [6,9,[12][13][14][15]. Few prospectively designed, randomized and controlled clinical trials have been conducted to explore the survival benefit of RT for early-stage ENKTL patients and current evidence mainly relies on retrospective studies and series case reports with small samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective analysis of more than 1,200 patients with stage I/II nasal NK/T-cell lymphoma showed that radiotherapy alone for the low-risk patients (age < 60 years; Eastern Cooperative Group performance score <2; stage I disease; normal lactate dehydrogenase, LDH; no primary tumor invasion into surrounding tissue) was associated with a relapse rate of 19%. 47 On the other hand, for high-risk patients, addition of chemotherapy to radiotherapy conferred survival advantage. The 5-year overall survival (OS) for patients treated with radiotherapy followed by chemotherapy was 72.8%, compared with 57.9% in patients treated with radiotherapy alone.…”
Section: Treatment Of Stage I/ii Diseasementioning
confidence: 99%
“…Yang és mtsai retrospektív, multicentrikus tanulmányuk alapján IPI low-risk, 60 év alatti I. stádiumú betegcsoporton belül az ötéves PFS 79,2%, az OS 88,8% volt. Annak ellenére, hogy a betegség lokalizált volt, mégis jelentős számban figyeltek meg relapsust [14]. Agresszív lymphomákban, elsősorban DLBCL-ben alkalmazott IPIscore az ENKTL-betegek prognózisának precíz előrejel-zésében bizonyos korlátokat mutatott.…”
Section: Megbeszélésunclassified